The Karakteristik Budaya Jawa dan Madura dalam Perspektif Konseling Lintas Budaya: Tinjauan Literatur - Aldi Safrawi; Aprilia Putri Nur Hasanah; Fawaid Nuzil Furqoni; Jihan Milalid Yanur; Norfa Anisa; Riyadlatul Qamariyah; Rusmiyati (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2026)
This study aims to examine the characteristics of Javanese and Madurese cultures from a cross-cultural counseling perspective through a literature review. Indonesia, as a multicultural society, has diverse cultural backgrounds that influence how individuals think, behave, and communicate. Cultural differences between counselors and clients can become barriers in the counseling process if they are not well understood. This research uses a qualitative approach with a library research method by analyzing 22 relevant journal articles. The results show that Javanese culture emphasizes politeness, harmony, indirect communication, and conflict avoidance, while Madurese culture highlights assertiveness, openness, strong solidarity, and self-respect. These cultural differences affect communication patterns and how individuals express their problems in counseling sessions. Therefore, counselors need cultural understanding and multicultural competence to build effective relationships with clients and create a harmonious counseling process.